2020
DOI: 10.1007/s00439-020-02121-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive clinically oriented workflow for nucleotide level resolution and interpretation in prenatal diagnosis of de novo apparently balanced chromosomal translocations in their genomic landscape

Abstract: Comprehensive clinically oriented workflow for nucleotide level resolution and interpretation in prenatal diagnosis of de novo apparently balanced chromosomal translocations in their genomic landscape. Human Genetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Recently, a large‐insert genome sequencing study identified an apparently balanced translocation disrupting ANKS1B and WDR26 in a proband with a WDR26 ‐disease phenotype compatible 3 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large‐insert genome sequencing study identified an apparently balanced translocation disrupting ANKS1B and WDR26 in a proband with a WDR26 ‐disease phenotype compatible 3 …”
Section: Introductionmentioning
confidence: 99%
“…For CNVs, SVInterpreter offers an option of performing an overlap search between the query CNV and those curated in several public CNV databases and published datasets ( Supplementary Figure S2 ). The overlap specifications are similar to our previously published CNV-Content Tool ( David et al, 2020 ), which retrieves the best hit by database, with the respective overlap percentage and variant frequency. In addition to the SVInterpreter standard output table, a detailed overlap table is available for download on the output web page.…”
Section: Methodsmentioning
confidence: 99%
“…For clinical outcome prediction of a gene disruption, SVInterpreter retrieves gene-specific annotation data such as the LoF sensitivity, Genomics England PanelApp 15 data, its association with disorders and respective phenotypic overlap, animal model data, gene expression patters, and GWAS data. Concomitantly, the disruption of major genes by de novo BCA breakpoints leading to major AD developmental disorders, as retrieved by SVInterpreter, indicated the pathogenicity of ANKRD11 (OMIM *611192; proband DGRC0016) and WDR26 (OMIM *617424; proband DGRC0025) (David et al, 2020). In the abovementioned cases, the calculated similarity between the inputted phenotypes and of gene-associated disorders localized within the analyzed regions played a major part on the interpretation, where ANKRD11 PhenSSc was 2.64 (p 0.02; MaxSSc 4.01) and WDR26 PhenSSc was 2.31 (p 0.…”
Section: Retrospective Reevaluation Of Published Svsmentioning
confidence: 96%
See 2 more Smart Citations